The physical pretreatment of coir dust using autohydrolysis and rapid steam hydrolysis continuous extraction process (RASH) - Creencia, Eulalio C. (1987)
Autohydrolysis and Rapid Steam Hydrolysis (RASH) were investigated as a coir dust pretreatment for the production of microbial proteins. In autohydrolysis, lignin content increased as the reaction time and temperature were increased. The cellulose was partially degraded in a number of runs. The RASH pretreatment fractionated the lignin leaving a cellulose-rich mass in the reactor in all isothermal runs from 140 deg.C to 215 deg.C. Fermentation studies using candida utilis var. thermophila UPCC 2002 increased the protein content of the substrate. The results show that the autohydrolysis pretreatment is not suitable for coir dust. However, the RASH process disrupts the lignin polymer enhancing the bioconversion of cellulose to protein.
Typescript.
Thesis (M.S.)--University of the Philippines Diliman.
Keywords: Coir dust; Autohydrolysis; Rapid steam hydrolysis